The code of the school: discipline, respect, and survival in primarily black high schools - Bell, Charles (Journal of crime and justice, 2019)
Research on violence and culture highlights the presence of a street code that governs interpersonal communication and behavior in impoverished communities. I contribute to this literature by exploring how the social norms embedded within the Code of the Street influence violence in the academic setting. In this study, I explore the relationship between out-of-school suspension and social status in primarily black high schools (PBHSs). I also explore black students’ and parents’ perceptions of school discipline. Using qualitative methodology, I interview 60 black students and parents of black students who were suspended from a PBHS in southeast Michigan in the 2016-2017 school year. My findings suggest the informal social norms that are embedded within the Code of the Street pervade PBHSs to create the ‘code of the school’, which encourages students to seek physical altercations and out-of-school suspension as a strategy for earning respect, toughness, and elevated social status. Additionally, my findings suggest most parents are aware of the ‘code’ and instruct their children to engage in physical altercations when it is necessary to defend themselves. As a result, the code of the school renders out-of-school suspension as an ineffective deterrent to school violence.